Whole‐Tree Sap Flux in Quercus serrata Trees after Three Levels of Partial Sapwood Removal to Simulate Japanese Oak Wilt - Chandrathilake, G.G.T.; Tanaka, Nobuaki; Kamata, Naoto (John Wiley & Sons Ltd., 2016)
Plant transpiration plays a key role in the hydrological cycle in forested watersheds. Oak trees infested with Japanese oak wilt may show changes in transpiration even if they are still alive. However, to our knowledge, no study has shown changes in transpiration and its threshold for tree weakening. We hypothesized that whole‐tree sap flux would be reduced in surviving oak trunks owing to sapwood dysfunction; however, part of this reduction would be compensated by enhanced sap flux density (Fd) in the remaining functioning sapwood. To test this hypothesis, 25%, 50%, and 75% of sapwood was removed at breast height to simulate xylem dysfunction for nine Quercus serrata trees in a warm‐temperate secondary forest in Japan. Granier probes were used to measure the Fd of the treated and three control trees before and after the treatment. Even though tested trees were still alive until at least the end of the second growing season, external symptoms of weakening were detected in 75% treated trees. Analysis using a linear mixed model showed that whole‐tree sap flux was significantly reduced in all treatments. However, 25% and 50% treated trees showed significant Fd compensation, whereas 75% treated trees showed significantly smaller whole‐tree sap flux than the value expected from the treatment. These results suggest that the threshold of tree weakening lies between 50% and 75% of sapwood removal, above which the Fd compensation cannot be attained. Therefore, wholetree sap flux in infested but surviving trees varies with respect to the intensity of sapwood damage.
Keywords: ambrosia beetle; ambrosia fungi; Granier method; Platypus quercivorus; radial growth; Raffaelea quercivora; tree mortality; tree transpiration